2022
DOI: 10.1136/bmjopen-2021-059211
|View full text |Cite
|
Sign up to set email alerts
|

Scoping review exploring vocational rehabilitation interventions for mental health service users with chronic mental illness in low-income to upper-middle-income countries

Abstract: ObjectiveTo synthesise research published on vocational rehabilitation (VR) interventions offered in institutions, by occupational therapists, to mental health service users (MHSUs) with chronic mental illness, in low-income to upper-middle-income countries (L-UMIC).DesignThis scoping review used Arksey and O’Malley’s methodological framework, the Preferred Reporting Items for Systematic Reviews extension for Scoping Reviews and Joanna Briggs scoping review guidelines.Data sourcesWe searched PsycInfo, EBSCOhos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
4
0
1
Order By: Relevance
“…As demonstrated by Chimara et al, the prevailing institutional model of mental health services in LMICs often leads occupational therapists to prioritize service provision within institutions rather than in community settings. [7]. In contrast, social workers and psychologists displayed greater motivation to engage, learn, and participate in our program.…”
Section: Implementation Challenges and Solutionsmentioning
confidence: 93%
See 1 more Smart Citation
“…As demonstrated by Chimara et al, the prevailing institutional model of mental health services in LMICs often leads occupational therapists to prioritize service provision within institutions rather than in community settings. [7]. In contrast, social workers and psychologists displayed greater motivation to engage, learn, and participate in our program.…”
Section: Implementation Challenges and Solutionsmentioning
confidence: 93%
“…Despite nearly 60% of patients with severe mental illness in the United States expressing a desire to work, less than 2% have access to this evidence-based service [3]. While IPS has been developed and implemented in some Western countries, its development in the Middle East is limited [7]. In Iran, a developing country with an unemployment rate of 9.0% (amar.org.ir), the employment rate among people with severe mental illness is not well-documented.…”
Section: Introductionmentioning
confidence: 99%
“…The latter study in particular also points out that ‘No individual studies were identified for rehabilitation of speech and language disorders or cognition from LMICs’ given that 67% of stroke patients experience cognitive consequences. Finally, in a very recent review (Chimara et al, 2022), the authors describe the use of vocational rehabilitation only for chronic mental diseases in LMICs.…”
Section: Partmentioning
confidence: 99%
“…Despite all the research done there remains limited knowledge of supported employment interventions in LMICs. Although a scoping review has synthesised the existing evidence of vocational rehabilitation interventions being offered at institutions in LMICs [ 49 ], there is a dearth of evidence on support employment interventions in LMICs. This review, therefore, seeks to synthesize the existing literature pertaining to supported employment interventions in LMICs and document their impacts on persons with mental disabilities in the open labour market.…”
Section: Introductionmentioning
confidence: 99%